Feasibility and acceptability of a personalised script-elicitation method for improving evening sleep hygiene habits. Issue 1 (31st December 2023) - Mohideen, Anya; Bouvin, Clara; Judah, Gaby; Picariello, Federica; Gardner, Benjamin
ABSTRACT: Background: Attempts to improve evening sleep hygiene have overlooked that sleep preparation behaviours are often undertaken automatically with little awareness; that is, habitually. This mixed-methods study assessed aspects of the feasibility and acceptability of a novel behavioural intervention procedure ('script elicitation'), which encourages reflection on and reorganisation of the content and sequencing of habitual evening pre-sleep routines. Methods: The study was advertised via social media, and circular lists at a UK university. Twenty-four UK-based adults, reporting <6 h/night sleep, were recruited. At baseline, they completed sleep hygiene and quality measures, then participated in an online, one-to-one script elicitation interview. This involved the interviewer working with the participant to generate a fine-grained description of the content, organisation and variability of their typical pre-sleep routine, and plan a more sleep-conducive alternative routine to follow over the next week. One week later, participants completed sleep quality and hygiene measures, and a semi-structured interview about the intervention. Feasibility was assessed using quantitative data on response rates and attrition, and acceptability via sleep hygiene and quality scores, and qualitative data on intervention experiences. Results: All criteria were met. The target response rate was exceeded, none of the 24 participants dropped out, and sleep hygiene and quality scores either improved or remained stable. In interviews, all participants reported finding script elicitation useful. Script elicitation raised participants' awareness of habitual sleep hygiene routines, which gave many a newfound sense of autonomy over changing their sleep hygiene habits. While the habitual nature of existing routines obstructed change for some participants, most reported successfully changing aspects of their routine, and achieving behaviour, sleep and wellbeing improvements. Discussion: Script elicitation is a promising and acceptable method for tackling poor evening sleep hygiene habits. A more rigorous trial is warranted.